2020
DOI: 10.1128/aem.00742-20
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cefotaxime-Resistant Escherichia coli Isolates from Healthy Cattle and Sheep in Northern Spain: Phenotypic and Genome-Based Characterization of Antimicrobial Susceptibility

Abstract: In order to estimate herd-level prevalence of extended-spectrum β-lactamase/AmpC β-lactamase (ESBL/AmpC)- and carbapenemase-producing commensal Escherichia coli in ruminants in the Basque Country (northern Spain), a cross-sectional survey was conducted in 2014 to 2016 in 300 herds using selective isolation. ESBL-/AmpC-producing E. coli was isolated in 32.9% of dairy cattle herds, 9.6% of beef cattle herds, and 7.0% of sheep flocks. No carbapenemase-producing E. coli was isolated. Phenotypic antimicrobial susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 59 publications
1
24
2
Order By: Relevance
“…In conclusion, our study found a low incidence of AmpC-producing E. coli (11/78 enrichments from 7/26 farms) compared with European studies [14, 15, 37, 47], and no ESBL- or plasmid-mediated AmpC-producing E. coli were detected.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…In conclusion, our study found a low incidence of AmpC-producing E. coli (11/78 enrichments from 7/26 farms) compared with European studies [14, 15, 37, 47], and no ESBL- or plasmid-mediated AmpC-producing E. coli were detected.…”
Section: Discussioncontrasting
confidence: 42%
“…In previous cross-sectional studies carried out in Europe, of those E. coli isolates with an AmpC phenotype, 18–20 % harboured a mutation in the ampC promoter and the remainder carried the bla CMY-2 or bla CMY-4 gene [15, 37]. The mutations found in the promoter and attenuator regions of the E.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, in the eight EU countries supplying data on resistance in E. coli from calves to ampicillin, cefotaxime, ciprofloxacin and tetracycline for the period 2009-2017, there were 10 decreasing and 8 increasing trends [7]. A study in Spanish cattle herds tested E. coli isolated from healthy animals of all ages and found a significantly higher prevalence of resistance in dairy herds than in beef herds [26]. As much as 97.8% of all isolates were resistant to fourth-generation cephalosporins, 87.4% were resistant to third-generation cephalosporins, 70.4% to tetracycline, 70.4% to sulfamethoxazole, 47.4% to trimethoprim, 41.5% to ciprofloxacin, 28.9% to chloramphenicol and 23.7% to gentamicin.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only a handful of studies have reported the use of carbapenem agars as an initial screening step with the objective of detecting CP-producing GN bacteria in the gut of healthy cattle ( 11 , 52 ) or in milk from healthy cattle ( 53 ). In our study, screening with commercial carbapenem agars led to the isolation of mainly Pseudomonas spp., Ochrobactrum spp.…”
Section: Discussionmentioning
confidence: 99%